AI Based Drones for Security Concerns in Smart Cities - Rawat, Bhupesh; Bist, Ankur Singh; Apriani, Desy; Permadi, Nur Ihsan; Nabila, Efa Ayu (APTISI Transactions on Management (ATM), 2023)
The concept of a smart city has attracted the attention of all corners of the world. It updated with new technologies like AI, Blockchain, IoT, Drones, and many other things. Security in big cities is one of the main concerns, and everyone wants to feel safe 24/7 in every activity they do. In this paper, our research aims to highlight the use and importance of drones for intelligent city management, especially in the context of security. The drone security management flow is explained using the methods and technical details. This is followed by discussion on security concern in cities and how it is dealt with AI based drones.  In the conclusion section, it is discussed how emerging technology such as blockchain can help improve the management of smart cities. The use of drones supports the intelligent city concept with all its advantages in regional monitoring. Concept of smart cities is catching attention across the globe and it’s important as per context of emerging economies. In this paper, we discussed about the use of emerging technologies to make it possible. AI, Blockchain and Drone technologies are playing important role. Their significance and attention by researchers in exploring possibilities is shown in this paper. This paper will be very useful for researchers and engineers working in the same domain.